Geronimo Stilton #47 :Run for the hills, Geronimo! - Stilton, Geronimo (Scholastic, 2011)
Geronimo Stilton's peaceful trip to the beautiful Black Hills of South Dakota turns into a crazy treasure hunt with the entire Stilton clan in tow.